2004
DOI: 10.1255/jnirs.445
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Analysis of Ground Beef Using a Diode Array near Infrared Instrument on a Conveyor Belt

Abstract: In-line monitoring of the proximal composition of ground beef on a conveyer belt has been tested using a near infrared (NIR) reflectance instrument with a diode array detector. Sixty batches of coarsely ground beef were processed under industry conditions and monitored continuously. After removing signals originating from the belt itself, the remaining data were used to make partial least squares models for all samples at two different grinding sizes. The correlation coefficients were in the range 0.93-0.96, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Up to now, NIR technology has been dominated by reflectance instruments measuring one or more locations on the surface of the sample. On-line applications for meat products have traditionally been restricted to ground meat (Hildrum, Nilsen, Westard, & Wahlgren, 2004;Shackelford, Wheeler, & Koohmaraie, 2004). More recently NIR has also been applied to intact meat products.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, NIR technology has been dominated by reflectance instruments measuring one or more locations on the surface of the sample. On-line applications for meat products have traditionally been restricted to ground meat (Hildrum, Nilsen, Westard, & Wahlgren, 2004;Shackelford, Wheeler, & Koohmaraie, 2004). More recently NIR has also been applied to intact meat products.…”
Section: Introductionmentioning
confidence: 99%
“…ML models could be trained on static samples and directly transferred to the production line, but these are unlikely to be accurate when tested on moving materials. Several studies have shown this by focusing on the impact of motion conditions on acquired NIR spectra, for example, for monitoring minced beef [ 14 , 15 ], olive quality [ 16 ], food [ 17 ], and pharmaceutical powders [ 18 , 19 ]. For example, Dixit et al (2016) [ 15 ] noticed increased spectral noise, and Cama-Moncunill et al (2016) [ 17 ] showed changes to the intensity values of peaks under moving conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On-line applications in meat products have been mainly restricted to the determination of several components in ground meat (Hildrum, Nilsen, Westad, & Wahlgren, 2004;Isaksson, Nilsen, Tøgersen, Hammond, & Hildrum, 1996;Shackelford, Wheeler, & Koohmaraie, 2004;Tøgersen, Arnesen, Nilsen, & Hildrum, 2003;Tøgersen, Isaksson, Nilsen, Bakker, & Hildrum, 1999). NIR spectroscopy has been proved to be a useful technique to predict moisture, a w and NaCl in minced fermented sausages (Collell, Gou, Picouet, Arnau, & Comaposada, 2010).…”
Section: Introductionmentioning
confidence: 99%